CRM in Private Sector Entities in the Palestinian Market, and the Intervention of Social Media - Rashed, Samer Mahmoud (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Customer Relationship Management plays a critical role in the business world. Today the ability to manage customer relations, effectively can lead businesses to success in the competitive market with large numbers of rivals and substitutes. This thesis aims to measure the level of CRM, utilized by organizations in the Palestinian market. It will investigate the reasons for ineffective implementation and how social media and internet 2.0 could help in making CRM activities more effective and efficient. Keywords: CRM, Palestinian market, Customer Relationship Management implementation, CRM limitations, CRM and social media.

ÖZ : Müşteri İlişkileri Yönetimi iş dünyasında önemli bir rol oynamaktadır. Günümüzde müşteri ilişkilerini yönetmenin amacı çok sayıda rakipleri olan bir işyerinin son derece rekabetçi olan bu piyasada hayatta kalabilmesidir. Bu tezin amacları Filistin piyasasında Müşteri İlişkiler Yönetimini ölçmek, bunun verimli bir şekilde uygulanmamasının nedenlerini ve sosyal medya ve 2.0 internet Müşteri İlişkiler Yönetiminin faaliyetlerini daha etkin ve verimli hale gelmesine nasıl katkıda bulunabileceğini incelemektir. Anahtar kelimeler: Müşteri İlişkiler Yönetimi (MİY), Filistin Piyasası, MİY uygulaması, MİY sınırlamaları, MİY ve sosyal medya.
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2014. Supervisor: Assoc. Prof. Dr. Mustafa Tümer.
Keywords: Business Administration; Marketing Management; Customer relations - Management; Customer relations - Social media - Economic aspects; Business communication; CRM; Palestinian market; Customer Relationship Management implementation; CRM limitations; CRM and social media